Comparison of Multifrequency Narrow-Band CE-Chirp and Tone Burst Evoked Cervical Vestibular Evoked Myogenic Potentials - Neupane, Anuj Kumar; Lodha, Vidhi (Journal of the American Academy of Audiology, 2023)
Background Cervical vestibular evoked myogenic potentials (cVEMPs) are inhibitory myogenic responses that have commonly been elicited using a variety of stimuli. Yet the comparison of the effects of multifrequency tone bursts and narrow-band Claus Elberling chirps (NB CE-chirps) on cVEMPs has never been studied in homogeneous age groups.Purpose The present study focused on comparing the effect of multifrequency NB CE-chirps and tone bursts on the various parameters of cVEMP responses in normal-hearing younger adults.Research Design A within-group study design was applied, and purposive sampling was utilized for the collection of the data sample.Study Sample The present study involved the elicitation of NB CE-chirp and tone burst–evoked cVEMPs across four-octave frequencies in 25 normal-hearing younger adults.Results NB CE-chirp and tone burst evoked cVEMPs were found to have a 100% response rate for all frequencies except 4,000 Hz. Across frequencies, P1 and N1 latencies were seen to be significantly shorter for NB CE-chirps than tone bursts at 500 Hz and 1,000 Hz stimulation. No differences were seen in the P1N1 amplitudes and interaural asymmetry ratio between the two stimuli across all four-octave frequencies. Furthermore, we found a significantly higher number of ears tuned to NB CE-chirps than tone bursts at 500 Hz.Conclusions Comparative differences in the latencies of cVEMP responses between and within stimuli could be due to the variation in stimuli duration. Also, the difference in amplitudes across stimulation frequencies might have resulted due to the predominance of saccular responses at lower mechanical resonance frequencies. Thus, the tuning was also seen at 500 Hz and was relatively higher for NB CE-chirps than tone bursts.
Keywords: NB CE-chirp; tone bursts; cVEMP; octave frequency; frequency tuning